Is early activity resumption after paediatric concussion safe and does it reduce symptom burden at 2 weeks post injury? The Pediatric Concussion Assessment of Rest and Exertion (PedCARE) multicentre randomised clinical trial. Issue 5 (26th November 2021) - Ledoux, Andrée-Anne; Barrowman, Nick; Bijelić, Vid; Borghese, Michael M; Davis, Adrienne; Reid, Sarah; Sangha, Gurinder; Yeates, Keith Owen; Tremblay, Mark S; McGahern, Candice; Belanger, Kevin; Barnes, Joel D; et al.
Abstract : Objective: Investigate whether resuming physical activity (PA) at 72 hours post concussion is safe and reduces symptoms at 2 weeks, compared with resting until asymptomatic. Methods: Real-life conditions, multicentre, single-blinded randomised clinical trial, conducted in three Canadian paediatric emergency departments (ED). Children/youth aged 10–<18 years with acute concussion were recruited between March 2017 and December 2019, and randomly assigned to a 4-week stepwise return-to-PA protocol at 72 hours post concussion even if symptomatic (experimental group (EG)) or to a return-to-PA once asymptomatic protocol (control group (CG)). The primary outcome was self-reported symptoms at 2 weeks using the Health and Behaviour Inventory. Adherence was measured using accelerometers worn 24 hours/day for 14 days post injury. Adverse events (AE) (worsening of symptoms requiring unscheduled ED or primary care visit) were monitored. Multivariable intention-to-treat (ITT) and per-protocol analyses adjusting for prognostically important covariates were examined. Missing data were imputed for the ITT analysis. Results: 456 randomised participants (EG: N=227; mean (SD) age=13.3 (2.1) years; 44.5% women; CG: N=229; mean (SD) age=13.3 (2.2) years; 43.7% women) were analysed. No AE were identified. ITT analysis showed no strong evidence of a group difference at 2 weeks (adjusted mean difference=−1.3 (95% CI:−3.6 to 1.1)). In adherent participants, initiating PA 72 hours post injury significantly reduced symptoms 2 weeks post injury, compared with rest (adjusted mean difference=−4.3 (95% CI:−8.4 to –0.2)). Conclusion: Symptoms at 2 weeks did not differ significantly between children/youth randomised to initiate PA 72 hours post injury versus resting until asymptomatic; however, many were non-adherent to the intervention. Among adherent participants, early PA was associated with reduced symptoms at 2 weeks. Resumption of PA is safe and may be associated with milder symptoms at 2 weeks. Level of evidence: 1b. Trial registration number: NCT02893969 . Registry name: Pediatric Concussion Assessment of Rest and Exertion (PedCARE).